Role of Color Doppler in predicting perinatal outcome in preeclampsia - Roy, Anjuri J.; Bhosale, Archana A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia is one of the most common complications of pregnancy, which increases both fetal and maternal mortality and morbidity. Since preeclampsia is characterized by abnormal placenta formation leading to inadequate uteroplacental blood flow, Doppler ultrasonography can prove to be a useful tool to assess fetal outcome in PIH patients. Through this study, we sought to determine the perinatal outcome on the basis of Doppler changes seen in Umbilical and Middle Cerebral artery. Methods: This was a prospective study conducted from September 2014 to August 2017 in a tertiary care hospital where 150 singleton pregnant patients with preeclampsia were examined with Doppler ultrasound of the Umbilical artery and Middle cerebral Artery. Serial Doppler examination was performed and the results of the last Doppler examination within 10 days of delivery was considered. Perinatal outcome was studied in the form of perinatal death, mean APGAR at 1 and 5 minutes, birth weight and admission to Neonatal Intensive Care Unit (NICU). Results: Abnormal Doppler velocimetry of the umbilical artery (increased resistance, AEDV, REDV) were significantly associated with poor perinatal outcome in the form of low birth weight, APGAR of ≤7 at five minutes of birth and NICU admission. However, S/D ratio of the Middle cerebral artery could not positively predict poor perinatal outcome in this study. Conclusions: Doppler technology has provided the best opportunity for repetitive non-invasive hemodynamic monitoring in human pregnancy. Umbilical artery Doppler findings are slight better predictor of adverse perinatal outcome than an abnormal MCA.